(untitled) (American Journal of Islam and Society, 2014)
This collection of short stories and novel excerpts is the first of its kind to appear in English. Its twenty-seven stories are intended for the general public interested in exploring new horizons in fiction, although the fact that the book is published by a university press might limit public access. Tremors is a collection of fiction revolving around the ideas of migration, exile, hybrid identities, and coming to terms with these. The book is divided into three sections, each of which, according to the editors, revolves around a central theme. The stories in the first section, “American Homeland,” involve fictional accounts of the challenges of “immigration and assimilation in the United States” (p. xii). This, in fact, is not always the case. In Dena Afrasiabi’s “String,” for example, the female narrator, Forugh, is at home in the United States, for the only challenges facing her are the memory of her dead mother and the shadow of her sorrow-stricken Iranian father lurking in the background. Similarly, in Salar Abdoh’s “Fixer Karim,” it is the immigrant Heavy K who continues to ease past assimilation barriers in the United States, to the astonishment of the well-established Iranian-American narrator, so much so that the story ends with Heavy K appearing as the lead singer in a country band. In a number of stories, (e.g., Taha Ebrahimi’s “Family Trouble” or J. Kevin Shushtari’s “The Sweet Dry Fruit of the Lotus Tree”), in fact, the narrator’s family is well established and feels at home, sometimes with an American parent, until ghosts or guests from Iran upset the peace. The second section, “Iran, Land of Resilience,” has been so named because the setting of these stories is Iran, although not all of them entertain such a view about the land. One example is the excerpt from Zohreh Ghahremani’s Sky of Red Poppies, in which the dark days of oppression under the ...